Methicillin-resistant staphylococcus aureus in poultry and poultry meat: A meta-analysis - Ribeiro C.M. (2018)
Copyright © 2018 International Association for Food Protection.Methicillin-resistant Staphylococcus aureus (MRSA) is a bacterium that colonizes and infects various host species and has been found in the poultry production chain, raising concerns about possible transmission from farm to fork. The objective of this study was to use meta-analytical methods to estimate the pooled prevalence of MRSA in chickens, Turkeys, chicken meat, and Turkey meat. Three electronic databases (PubMed, LILACS, and SciELO) were searched to establish MRSA prevalence from 51 studies published from 2003 through May 2017. The heterogeneity was assessed, and the pooled MRSA prevalence was calculated by using the random effects model according to the method of DerSimonian and Laird. Pooled MRSA prevalence (95% confidence interval [CI]) in Turkeys, Turkey meat, broilers, and chicken meat was 36% (1 to 78%), 13% (1 to 28%), 5% (2 to 9%), and 5% (3 to 8%), respectively. South America had the highest MRSA prevalence (27%; 95% CI, 17 to 37%), and North America had the lowest (1%; 95% CI, 0 to 2%). Livestock-associated MRSA has been isolated from poultry and poultry meat, indicating that this variant can spread from farm to fork. The presence of MRSA in poultry and poultry meat poses risks to public health, and steps should be taken to mitigate the contamination and spread of this bacterium along the poultry production chain.